Millennial-Assisted Liposuction: The Next-Generation/Future Technique. Issue 2 (August 2020) - Barnes, Connor; Weinstein, Brielle; Robertson, Ellen; Clark, Clifford
Abstract : Abstract: Over the past 6 decades through innovation, creativity, ingenuity, and hard work, liposuction is now one of the most popular cosmetic procedures around the world. Several different liposuction technologies now exist, which include suction-assisted lipectomy, power-assisted liposuction, and so on. We have devised a new technique geared toward the incoming Generation Y surgeon called millennial-assisted liposuction. With such great advances in current liposuction techniques, one might ponder the need to introduce a new technique. This may become more common as the "Me Generation" sets forth in the working community and takes over for the prior generation of plastic surgeons. This article was written and developed by a millennial and the senior author, a nonmillennial, to help conform to the changing dynamic of incoming plastic surgeons. The technique was developed to solve the problem regarding millennials requiring constant reinforcement, around-the-clock assistance, immediate feedback, work-hour limits, frequent breaks, and lack of trophies.